Upaya Peningkatan Nilai Religius Pada Anak-Anak Desa Kandri Melalui Implementasi Taman Pendidikan Al-Qur'an Di Desa Kandri Kecamatan Gunungpati Kota Semarang - Isna Rahmah Sabila; Putri Merlinda; Hanif Jamaluddin Ahmad; Litajzia Jaza ‘Anil Husna; Arina Haqia; Lenni Khotimah harahap (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Religious education for children at TPQ Kandri Village plays a crucial role in shaping their personality and faith. This study discusses the implementation of religious values through various interactive and fun learning methods, allowing children to internalize Islamic teachings effectively at TPQ. The results show that the religious values implemented in the TPQ of Kandri Village children, such as mutual respect, worship, self-confidence, social discipline, discipline, honesty, respect for previous scholars, and the cultivation of the value of Ahlu Sunah Waljamaah teachings, succeeded in increasing their religious values. This activity was conducted in Kandri Village, Gunungpati Subdistrict, Semarang City. This research is expected to provide insight into the effectiveness of the approach applied in educating children in the TPQ environment, as well as its impact on the formation of their religious character.